2003
DOI: 10.1080/07399330390199384
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Care in Botswana: Experiences of Older Women and Young Girls

Abstract: In this exploratory and descriptive study we investigated the experiences of and impact on young girls and older women caring for family members living with HIV/AIDS and other chronic and terminal illnesses at home in three districts of Botswana. Using qualitative research methods, we conducted 70 interviews with family caregivers and key informants such as community home-based care (CHBC) team members and government officials. Older women reported feeling overwhelmed with the magnitude and multiplicity of tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 3 publications
3
71
1
Order By: Relevance
“…23 Tiredness and psychosomatic complaints from the caregivers were common in this and other studies. 1,6,19 These included headache, abdominal pain, chest pain and anorexia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…23 Tiredness and psychosomatic complaints from the caregivers were common in this and other studies. 1,6,19 These included headache, abdominal pain, chest pain and anorexia.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,22 In Botswana, 1 it was found that elderly caregivers did not use the care package they were provided with because they felt that using gloves would imply that they do not love the person in their care. In contrast, caregivers in a Namibian study 7 expressed anger at the risk they were exposed to.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations